P-38 Psychosocial work characteristics and low back pain in nursery school workers in Japan. (14th March 2023) - Shi, Xuliang; Aoshima, Megumi; Iida, Tadayuki; Hiruta, Shuichi; Ono, Yuichiro; Ota, Atsuhiko
Abstract : Introduction: Recent studies have indicated the potential influence of psychosocial work characteristics on low back pain (LBP), a common musculoskeletal problem. We aimed to identify psychosocial work characteristics that influenced LBP in school workers. Methods: We conducted a prospective cohort study with one year of observation. The baseline sample was 444 nursery school workers in Nagoya, Japan. A questionnaire survey was used for data collection. General characteristic information was collected and used the question 'Where are you currently feeling LBP?' was used to diagnose LBP. Logistic regression analysis was used to examine the prospective association of the psychosocial work characteristics, i.e., high job strain, low social support, effort-reward imbalance, and overcommitment, at baseline and LBP one year later. Results: At baseline, 270 (60.8%) subjects suffered from LBP. One year later, 208 provided information on LBP; 176 (84.6%) suffered from the persistence of LBP. Those with low social support at baseline showed a higher prevalence of persistent LBP than those without (89.9% vs. 80.0%). The adjusted odds ratio (95% confidence interval) of low social support at baseline for the persistence of LBP was 2.43 (1.01–5.87). Of 150 subjects who were free from LBP at baseline and provided information on LBP one year later, 45 (30.0%) experienced the onset of LBP. None of the psychosocial work characteristics was associated with the onset of LBP. Conclusions: In this prospective cohort study, low social support was not related to the onset of LBP but was associated with the persistence of LBP. High job strain, effort-reward imbalance, or overcommitment had no discernible effect on LBP.